Analysis of the Effect of Market Structure and Operational Efficiency on Banking Financial Performance in the Founding Countries of ASEAN in 2013-2015 - Dwi Yullianda Ginting (International Journal on Social Science, Economics and Art, 2021)
This study aims to analyze the effect of Market Structure and Efficiency Operational on financial performance (ROA) bank in the country of ASEAN Founder for the period of 2013-2015. The population of this study were 71 commercial banks operating in Indonesia, Malaysia, Singapore, Thailand and Philippine. The total of sample are 26 banks with purposive sampling method. Independent variables in this study are the market share, market concentration, NIM, and BOPO ratios. Data used in this research is secondary data that shaped panel data (pooling data). Fixed effect model or known as least square dummy variable (LSDV) used as analysis method in this research. Based on the result of F test is known that there is a significant effect of the variable market share, market concentration, NIM and BOPO ratios simultaneous on ROA bank. The result also showed that 85.4% ROA is affected by variable market share, market concentration, NIM and BOPO ratio while the remaining 14.2% is explained by other variables that aren’t included in the model. Based on t test can be seen that there is a significant effect of the variable market share, NIM, and BOPO on ROA. For market concentration has no significant effect on ROA bank. The implication of this research on banking in the country of ASEAN Founder is the increase of market share, NIM ratio and BOPO ratios will improve financial performance.